Elevating leadership : innovative teaching methods for developing future leaders - Kohn, Pelin (Emerald Publishing Limited, 2024)
In the rapidly evolving landscape of leadership education, the importance of innovative pedagogical practices cannot be overstated. Demands on leaders continue to develop and a diverse and dynamic skill set is crucial for navigating the complexities of the modern workplace. Leaders are expected to demonstrate adaptability, emotional intelligence, ethical decision-making, collaborating across cultures and technologies. To cultivate these essential skills, traditional teaching methods may not be sufficient, necessitating the integration of innovative pedagogies to unlock the full potential of leadership learners. Elevating Leadership explores the critical importance of innovative pedagogical practices in a world where leadership demands are rapidly changing - using experiential learning, simulations, and technology-enabled tools, Pelin Kohn provides learners with real-world scenarios, fosters practical insights, and enhances problem-solving skills. The competency-based leadership model as a new development through innovative pedagogical practices allows learners to acquire tangible skills and behaviours that can be immediately applied in real-world leadership scenarios, ensuring both theoretical and practical development is achieved. Elevating Leadership demonstrates how to cultivate a growth mindset in leadership learners, resulting in adaptable and resilient leaders who can navigate change and uncertainty successfully.
Keywords: Leadership -- Study and teaching.; Business & Economics -- Leadership.; Management: leadership and motivation.; elektronické knihy; electronic books